Optimization of inulinase production by a newly isolated strain Aspergillus flavus var. flavus by solid state fermentation of Saccharum arundinaceum. (November 2019) - Das, Deblina; Selvaraj, Raja; Ramananda Bhat, M.
Abstract: The present study deals with the use of mangrove soil, a new source for the isolation of an inulinase producing strain followed by the enzyme production and optimization using hardy sugarcane, " Saccharum arundinaceum ", a novel substrate. Four fungal isolates were obtained from the primary screening in inulin media. In the secondary screening, only Aspergillus flavus var. flavus strain ATCC 16883, a new strain, showed the zone of hydrolysis surrounding the fungal growth on the inulin medium plate. The action pattern of inulinase was determined by thin layer chromatography which confirmed it to be exoinulinase in nature. Solid state fermentation of A. flavus ATCC 16883 using Saccharum arundinaceum showed a maximum inulinase activity of 3.48U/gds after 96 h. The inulinase nature of the enzyme was confirmed by the resultant I/S ratio of 2.56. Central Composite Design (CCD) was used to optimize the media components and obtain a quadratic model using the five significant nutrients namely, inulin, K2 HPO4, (NH4 )2 SO4, KH2 PO4 and NaCl. Using the optimum conditions of (g/gds) inulin- 0.1, K2 HPO4 - 0.05, (NH4 )2 SO4 - 0.002, KH2 PO4 - 0.005 and NaCl- 0.02, the inulinase activity was determined as 8.57U/gds which was 2.50-fold higher than the initial unoptimized conditions. Graphical abstract: Image 1 Highlights: Aspergillus flavus var. flavus strain ATCC 16883, a new inulinase producer was isolated from mangrove soil, a new source. Saccharum arundinaceum proved to be an efficient substrate for solid state fermentative production of inulinase. Central Composite Design was used to optimize the five media components namely, inulin, K2 HPO4, (NH4 )2 SO4, KH2 PO4 and NaCl. Under the optimum conditions, a 2.50-fold increase in inulinase activity was obtained.